Tourist decision to visit a destination through h eWOM information: an UTAUT approach study in Indian context / Kamaleswar Boro ... [et al.] - Boro, Kamaleswar; Goswami, Chandan; Kumar, Narendra; Sharma, Swati; Das, Sukriti (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2024)
In today's digital age, eWOM has emerged as a powerful tool in shaping travel decisions and influencing consumer choices. The present study highlights the growing interest in eWOM as a mediator in tourism research and the application of the UTAUT model in studying this phenomenon. The study is descriptive and analytical in design and uses primary data from 359 respondent’s tourist in India. Structured Equation Modelling (SEM) has been performed using SPSS AMOS to investigate the relationship between the constructs. By synthesizing existing knowledge as well as performing empirical analysis of data collected, this study contributes to an understanding of how eWOM influences tourists' decision- making processes and offers implications for both practitioners and researchers in the field of tourism. Particularly, the findings highlight how UTAUT constructs influence eWOM adoption to make travel decisions as well as how eWOM mediates the relationship of UTAUT constructs with tourist intention to visit a destination.